ARTIFICIAL INTELLIGENCE APPLICATIONS AND THEIR ROLE IN ENHANCING STRATEGIC IMPROVISATION ANALYTICAL STUDY TO SEE A SAMPLE OF ADMINISTRATIVE LEADERS PRESIDENCY OF AL- FURAT AL -AWSAT TECHNICAL UNIVERSITY (World Economics and Finance Bulletin, 2026)
This study aims to analyze the role of artificial intelligence (AI) in enhancing strategic improvement within educational organizations through an applied study at Al-Furat Al-Awsat Technical University. The research relied on a purposive sample of administrators at the university, as They are the group most closely connected to the research topic and strategic decision-making, to determine their awareness of the importance of AI and its impact on enhancing strategic improvement. The independent variable AI was measured through three main dimensions: expert systems, neural networks, and algorithms. The dependent variable Strategic Improvement was measured using four dimensions: strategic flexibility, strategic vigilance, innovation, and entrepreneurial orientation The research sample consisted of (75) adminIstrative leaders at Middle Euphrates Technical University. The questionnaires were distributed to them, which included approved measures for the research variables. The research hypotheses related to the correlation and influence relationships between variables were tested using a set of appropriate statistical methods. The results of the statistical analyses showed a StatIstically SignificanT correlation and influence relationship between artificial intelligence and strategic improvement, both at the macro level and at the sub-dimension level. The research concluded that artificial intelligence tools represent a fundamental factor in enhancing strategic improvement at the university under study, as they support organizational flexibility, promote innovation, and improve the ability to respond strategically to environmental changes
Keywords: Artificial intelligence; Strategic improvIsation; adminIstrative leadership